Unravelling polar lipids dynamics during embryonic development of two sympatric brachyuran crabs (Carcinus maenas and Necora puber) using lipidomics - Rey, Felisa (2017)
Embryogenesis is an important stage of marine invertebrates with bi-phasic life cycles, as it conditions their larval and adult life. Throughout embryogenesis, phospholipids (PL) play a key role as an energy source, as well as constituents of biological membranes. However, the dynamics of PL during embryogenesis in marine invertebrates is still poorly studied. The present work used a lipidomic approach to determine how polar lipid profiles shift during embryogenesis in two sympatric estuarine crabs, Carcinus maenas and Necora puber. The combination of thin layer chromatography, liquid chromatography – mass spectrometry and gas chromatography – mass spectrometry allowed us to achieve an unprecedented resolution on PL classes and molecular species present on newly extruded embryos (stage 1) and those near hatching (stage 3). Embryogenesis proved to be a dynamic process, with four PL classes being recorded in stage 1 embryos (68 molecular species in total) and seven PL classes at stage 3 embryos (98 molecular species in total). The low interspecific difference recorded in the lipidomic profiles of stage 1 embryos appears to indicate the existence of similar maternal investment. The same pattern was recorded for stage 3 embryos revealing a similar catabolism of embryonic resources during incubation for both crab species.